EFFECT OF ELECTROSTATICALLY LINKED IONIZABLE GROUPS ON SULPHYDRYL REACTIVITIES OF HEMOGLOBINS (1990)
The kinetics of the reactions of two sulphydryl reagents with the CysF9(93)β sulphydryl group of various human and animal hemoglobin derivatives have been studied as a function of pH at 20°C, at an ionic strength of 0.05 M. A quantitative analysis of the data was possible only for the 2,2'-dithiobispyridine data. For the 5,5'-dithiobis[2-nitrobenzoic acid] data, the equation relating the apparent second order rate constant to the model parameters was complex and therefore not useful for quantitative analysis. However, interesting results were observed for the 5,5'-dithiobis [2-nitrobenzoic acid]reaction. As a general conclusion, it is suggested that the reactivity of the CysF9(93)β sulphydryl , depends on two factors: the conformation of the sulphydryl group and the electrostatic effects of the charged ionizable groups on the protein. In order to determine the nature of the charged groups affecting sulphydryl reactivity, the reaction of hemoglobin with another sulphydryl reagent, was studied by potentiometric difference titration as a function of pH at 20°C and ionic strength O.05M. Differences were observed for various derivatives for the parameter Δh+ the number of protons released per sulphydryl group reacted. These differences reflect differences in tertiary structure between the derivatives studied rather than differences in quaternary structure.